The effects of english curriculum achieved by teachers of sixth grade from Nuevo Vedado and Varital Elementary Schools, David, Chiriquí, 2010 - Aguirre Guerra, Michelle Lisbeth; Atencio De León, Yanela Yaneth; De Gracia, Edward (David, Panamá : UDELAS, 2010)
Our research aims to provide strategies to strengthen the study and independent learning and continuing application in the entity intends to assist in the ongoing education reform process and thereby contribute to improving the quality of education that is offered in the entity.
GENERAL INDEX Dedication Acknowledgment Chart index Graphs Introduction CHAPTER I: THE PROBLEM OF RESEARCH CONDUCTED IN THE NUEVO VEDADO SCHOOL, AND VARITAL SCHOOL CHAPTER II: THEORETICAL FRAMEWORK 2.1. The english curriculum achieved from Nuevo Vedado, and Varital Elementary School 2.2. Effects in students from Nuevo Vedado and Varital Elementary School followed versus not followed the curriculum 2.3. Organization of curriculum from Nuevo Vedado and Varital Elementary Schools CHAPTER III: METHODOLOGICAL FRAMEWORK CHAPTER IV: ANALYSIS AND INTERPRETATION OF THE RESULT CONCLUSIONS RECOMMEDATIONS BIBLIOGRAPHY ANNEXES
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Inglés
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- TESIS DE LICENCIATURA; CURRICULUM -- TESIS DE LICENCIATURA; FACULTY OF SOCIAL AND SPECIAL EDUCATION; ENGLISH SCHOOL; LICENCIANTURA EN DOCENCIA EN INGLÉS; NUEVO VEDADO ELEMENTARY SCHOOL; VARITAL ELEMENTARY SCHOOL